Quality assurance in MR image guided adaptive brachytherapy for cervical cancer: Final results of the EMBRACE study dummy run. Issue 3 (December 2015) - Kirisits, Christian; Federico, Mario; Nkiwane, Karen; Fidarova, Elena; Jürgenliemk-Schulz, Ina; de Leeuw, Astrid; Lindegaard, Jacob; Pötter, Richard; Tanderup, Kari
Abstract: Purpose: Upfront quality assurance (QA) is considered essential when starting a multicenter clinical trial in radiotherapy. Despite the long experience gained for external beam radiotherapy (EBRT) trials, there are only limited audit QA methods for brachytherapy (BT) and none include the specific aspects of image guided adaptive brachytherapy (IGABT). Methods and materials: EMBRACE is a prospective multicenter trial aiming to assess the impact of (MRI)-based IGABT in locally advanced cervical cancer. An EMBRACE dummy run was designed to identify sources and magnitude of uncertainties and errors considered important for the evaluation of clinical, and dosimetric parameters and their relation to outcome. Contouring, treatment planning and dose reporting was evaluated and scored with a categorical scale of 1–10. Active feedback to centers was provided to improve protocol compliance and reporting. A second dummy run was required in case of major deviations (score <7) for any item. Results: Overall 27/30 centers passed the dummy run. 16 centers had to repeat the dummy run in order to clarify major inconsistencies to the protocol. The most pronounced variations were related to contouring for both EBRT and BT. Centers with experience in IGABT (>30 cases) had better performance as compared to centers with limited experience. Conclusion: The comprehensive dummy run designed for the EMBRACE trial has been a feasible tool for QA in IGABT of cervix cancer. It should be considered for future IGABT trials and could serve as the basis for continuous quality checks for brachytherapy centers.